Taxonomic significance of seed and leaf micromorphology in Saponaria (Caryophyllaceae) - Erdi̇r, Meltem; Ataşlar, Ebru (Phytotaxa, 2022)
The seed and leaf structures of some species belonging to the genus Saponaria (Caryophyllaceae) were examined using SEM. These species were: S. calabrica, S. dalmasii (endemic), S. glutinosa, S. halophila (endemic), S. karapinarensis (endemic), S. kotschyi (endemic), S. mesogitana, S. officinalis, S. orientalis, S. pamphylica (endemic), S. picta (endemic), S. pinetorum var. elatior (endemic), S. prostrata subsp. anatolica (endemic), S. prostrata subsp. calvertii, S. prostrata subsp. prostrata (endemic), S. pumilio, and S. tridentata. The results obtained show that the micromorphology of the seed are useful to distinguish the studied species. Four groups can be distinguished using the number of seed per capsule. In addition, the shape of the seed, microsculpture, shape and margin of testa cells were found as important characteristics to identify the various species. Leaf anatomy reveals that trichome type and mesophyll symmetry define significant differences between the studied species.